A presunção de inocência e a recente mudança jurisprudencial do Supremo Tribunal Federal sobre o tema - Dantas, Antonio Carlos (Universidade Federal Rural do Semi-Árido, 2018)
The present article intends to make a (synthetic) exposition of the recent jurisprudential change in the scope of the STF with respect to the application of the presumption of innocence principle described in art. 5, LVII of the Federal Constitution and the possibility of complying with a provisional sentence following a decision of the second instance. In the research, we briefly discussed the historical evolution of the principle of presumption of innocence, analyzing its conceptualization and inclusion in the Brazilian order, passing through the concept of unappealable traffic in the context of the theme. We summarized the changes that occurred in the Supreme Court's jurisprudence from HC 84.078MG to HC 126.292-SP, as well as from the judgment of the precautionary measures in ADC's 43 and 44 of DF, which supported the thesis signed in HC 126.292-SP, and also , the general repercussion given to the topic in ARE 964.246-SP. We discuss the judicial activism of the Supreme Court to effect a constitutional mutation different from what is stated verbatim in art. 5, LVII of the Magna Carta, analyzing if this would be possible in the constitutional legal order. There was an analysis of data on the consequences in the Brazilian criminal system with the jurisprudential change of the STF in the hypothesis of provisional fulfillment of sentence, as well as we brought to the bail the statistics of the STJ in reference to the reform of criminal decisions within that Court. In the end, we discuss the expectations of new case law, signed in HC 126.292-SP (2016), ADC's 43 and 44 and ARE 964.246.
Artigo Acadêmico
Keywords: Presunção de inocência; Execução provisória da pena; Trânsito em julgado; Ativismo judicial; Presumption of innocence; Provisional execution of sentence; Final judgment; Judicial activism; CIENCIAS SOCIAIS APLICADAS::DIREITO